(untitled) (Estudios Sociales, 2023)
This article addresses the consequences of dispossession on labor trajectories of urban-dwelling Mapuche women and their labor situation as viewed from their own perspective in southern Wallmapu, between 1985–2020. These women belong to two distinct generations engaged in labor market in Fütawillimapu (Great Lands of the South). By means of nütram, a personal-social history is reconstructed for each worker, presenting their labor trajectories in a time-spatial sequence: settlement, placement, and experience regarding entry into and exit out of labor field. Thus, logics of bodily dispossession are revealed to be articulated by the effects of territorial dispossession, both of these coexisting within a third one, namely political dispossession, which persists in relegating the role of indigenous peoples’ historicity in labor.